First record of Cynipidae from Myanmar with description of a new species of Lithosaphonecrus (Hymenoptera: Cynipidae: Synergini) - Ide, Tatsuya; Aung, Mu Mu; Tanaka, Nobuyuki (Zootaxa, 2020)
A new cynipid species, Lithosaphonecrus mindatus Ide, Aung & Tanaka, sp. nov., is described from Chin State, northwestern Myanmar. This is the first record of Cynipidae from this country. The new species emerged from a bud gall of Lithocarpus thomsonii. The new species’ morphological features closely resemble L. arcoverticus Liu, Zhu & Pang, but differ from the latter due to the presence of a broad foveal septum on the mesoscutellum and short triangular median mesoscutal impression and absence of the anteroadmedian signum on the mesoscutum. Partial sequences of cytochrome c oxidase subunit I region (614 bp) show a 14–15% difference between the new species and other congeners.